Pengaruh Variasi Kecepatan Hembusan Udara Terhadap Temperatur, Daya Output dan Efisiensi Pada Pendinginan Panel Surya (Infotekmesin, 2020)
The rapid development of technology, sunlight can be converted into electrical energy. But there are problems that arise in the performance of solar panels, one of which is the panel temperature is too high. Therefore to overcome the decrease in performance, the panel temperature needs to be maintained. In this study aims to analyze the temperature settings on solar panel cooling using variations in air velocity to improve photovaltic performance. Solar simulators is used in this ekperiment and carried out in a closed room conditions. solar panel is placed in a special box called a cooler box and four thermocouples are placed at the top of the panel and 2 others at the bottom of the panel to evaluate the temperature changes that occurs on the panel. An air blower is combined with an anemometer to provide variations in air velocity for cooling the panels. From the results of solar panel testing without cooling obtained in the temperature range of 38 - 52.875â°C produces electrical efficiency ranging from 3.014 - 3.134%. Whereas in testing using cooling with varying air velocity of 2, 3, 4, and 5 m/s in the temperature range of 33.43 -40.5Â°C produces electrical efficiency ranging from 3.106 - 3.206 %.